2020
DOI: 10.1007/s11686-020-00238-7
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology and Associated Risk Factors of Toxoplasma gondii in Hemodialysis Patients

Abstract: Purpose Immunocompromised patients may be at risk for reactivation of the toxoplasmosis infection, because of defection in cell-mediated immunity. Therefore, early diagnosis would be highly desirable in these individuals. This case-control study was designed to increase information about toxoplasmosis in hemodialysis (HD) patients in Guilan province, Iran. Methods The study was performed among 150 patients and 150 controls referred to hospitals of Guilan University of Medical Sciences during 2018-2019. Questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…were higher in the age group (43-51) year, .the reason for this is that the total prevalence of antibodies has gradually increased with age and patients weakened immunity . With regard to the effect of educational level factor, this study no statistically significant differences between levels of education, both between patients and healthy people , were showed that educational level (6-12) showed significantly higher serum positivity (P = 0.0068) than their peers (Odds ratio:10,000).This result is identical to Saadat [30], a study were seroprevalence of T. gondii infection did not vary significantly with educational level. Despite this result, most children suffer from weak immune systems and are therefore most susceptible to toxoplasmosis at this stage, they can also contract this infection by accidentally swallowing soil or eating undercooked fruits or vegetables contaminated with cat feces from a cat with toxoplasmosis.…”
Section: Discussionsupporting
confidence: 70%
“…were higher in the age group (43-51) year, .the reason for this is that the total prevalence of antibodies has gradually increased with age and patients weakened immunity . With regard to the effect of educational level factor, this study no statistically significant differences between levels of education, both between patients and healthy people , were showed that educational level (6-12) showed significantly higher serum positivity (P = 0.0068) than their peers (Odds ratio:10,000).This result is identical to Saadat [30], a study were seroprevalence of T. gondii infection did not vary significantly with educational level. Despite this result, most children suffer from weak immune systems and are therefore most susceptible to toxoplasmosis at this stage, they can also contract this infection by accidentally swallowing soil or eating undercooked fruits or vegetables contaminated with cat feces from a cat with toxoplasmosis.…”
Section: Discussionsupporting
confidence: 70%
“…Exposure to T. gondii may cause acute or chronic damage to the kidney, triggering injury, which can affect the exposure over their life course. Prior studies have found a link between undergoing dialysis and an increased rate of T. gondii infection [35,36], but there has not been a thorough investigation of the association of Toxoplasma with CKD in the USA population. Thus, the purpose of this study was to investigate this association along with common risk factors of CKD.…”
Section: Association Of Toxoplasma and Ckd After Adjusting For Co-variatesmentioning
confidence: 99%
“…However, our records were lower than those of Hamza et al [9] , who discovered T. gondii seropositivity among adult hemodialysis patients (61.7%) and renal transplant recipients (70.0%) in Alexandria Governorate. Similarly, it is lower than rates in other nations such as Iran (74-76.8%) [1,7] , Turkey (56.0%-76.5%) [22] , and Mexico (56.7%) [23] .…”
Section: Discussionmentioning
confidence: 89%
“…Toxoplasmosis is a zoonotic illness caused by T. gondii, an obligate intracellular protozoan [1] . It is a largely undiagnosed, highly neglected disease that can be fatal in humans and animals worldwide [2] .…”
Section: Introductionmentioning
confidence: 99%